The Performance of Real-Time Polymerase Chain Reaction in Patients with Scanty Positive Acid-Fast Bacilli Sputum Smear in Diagnosis of Pulmonary Tuberculosis: 5-Year Retrospective Study - Kanchanasuwan, Siripen; Kositpantawong, Narongdet (Siriraj Medical Journal, 2021)
Objective: To assess the performance of real-time polymerase chain reaction (RT-PCR) to diagnosis pulmonary tuberculosis in patients with scanty positive acid-fast bacilli sputum smears, in a single hospital. Materials and Methods: All patients, who had scanty positive AFB sputum smears in Songklanagarind Hospital; between 2015 and 2019 were included. Demographic data, clinical data, radiographic findings, RT-PCR and mycobacterial culture results were reviewed. Results: From a total of 269 patients reporting scanty AFB smears, 116 patients (43.1%) had cultures confirmed as M. tuberculosis. From overall, samples from 92 patients with scanty AFB smear were processed for RT-PCR. There were 26 (28.3%) isolates having positive RT-PCR test results. Of these 26 isolates that RT-PCR positive, 25 (96.2%) were culture positive, while only 1 (3.8%) were culture negative. A remaining 66 samples that RT-PCR negative, 15 (22.7%) were culture positive for tuberculosis. Using mycobacterial cultures as the gold standard, the sensitivity, specificity, positive predictive value and negative predictive value of RT-PCR were 62.5%, 98.1%, 96.2%, and 77.3%, respectively. Pulmonary consolidation and cavity on chest radiograph were associated with the growth of M. tuberculosis, with an OR of 2.3 (95% C.I. 0.26-0.73) and 3.4 (95% C.I. 1.2-9.9), respectively. Conclusion: Less than half of the patients with scanty smears had culture-confirmed tuberculosis; RT-PCR also has low sensitivity. Consequently, a negative RT-PCR does not exclude tuberculosis; especially in cases of a high index for clinical suspicion. Radiographic findings; including pulmonary consolidation and cavities, are helpful predictors for supporting this diagnosis.